Case Report: Conjunctivitis in Children - Kaherma Sari; Thalia Shalsabillah (International Journal of Health and Medicine, 2024)
Conjunctivitis is an inflammation of the conjunctiva, the mucous membrane covering the back of the eyelids and the eyeball, which can be acute or chronic. This condition is characterized by conjunctival hyperemia, edema, and discharge. Causes of conjunctivitis include bacteria, chlamydia, allergies, viruses, and systemic diseases. The incidence of conjunctivitis varies by age, sex, and season. Although slightly more common in women in emergency departments, the seasonal pattern of conjunctivitis is consistent across regions. Allergic conjunctivitis, which affects 15-40% of the population, is most common in the spring and summer. Bacterial conjunctivitis is most common from December to April. Acute bacterial conjunctivitis is generally self-limited, with symptoms lasting 1-3 days if treated appropriately, but can last 10-14 days if left untreated. Staphylococcal and gonococcal conjunctivitis can lead to chronic complications or serious problems such as corneal perforation. Viral conjunctivitis usually gets worse in 4-5 days and resolves in 1-2 weeks. Complications are rare but can include corneal problems and life-threatening conditions such as meningitis or sepsis.